Adsorption-induced deformation of hierarchical organised carbon materials with ordered, non-convex mesoporosity. (18th August 2021) - Ludescher, Lukas; Morak, Roland; Braxmeier, Stephan; Balzer, Christian; Putz, Florian; Busch, Sebastian; Hüsing, Nicola; Reichenauer, Gudrun; Gor, Gennady Y.; Paris, Oskar
Abstract : Adsorption-induced deformation of monolithic, hierarchically organised porous carbon materials exhibiting non-convex mesoporosity between hexagonally arranged carbon nanorods was investigated with adsorption dilatometry and small-angle neutron scattering (SANS). n-pentane with zeroscattering length density was used as an adsorbate for SANS. To assess the influence of micropores on deformation, three samples with different degrees of CO2 activation were investigated. The measured strain isotherms show distinct differences as compared to strain isotherms from systems with convex cylindrical mesopores. Strain isotherms deduced from SANS exhibit three different regimes, which are ascribed to a film phase at low-, a bridged phase at intermediate-, and a filled phase at high relative pressures. Evaluating the pore load moduli from SANS and dilatometry, we find an apparent stiffening of the samples on the mesoscale upon activation. We assume that the stiffness of the linkers between the nanorods increases with activation, whereas the elastic modulus of the carbon nanorods is reduced. The results demonstrate that adsorption-induced deformation in these materials with non-convex, interconnected mesopore space strongly depends on structural disorder within and in between the carbon nanorods, and emphasise the importance of strain isotherms as a source of complementary information to classical adsorption analysis. GRAPHICAL ABSTRACT: UF0001